RSRP: A Robust Secure Routing Protocol in MANET - Sinha Ditipriya (Foundations of Computing and Decision Sciences, 2014)
In this paper, we propose a novel algorithm RSRP to build a robust secure routing protocol in mobile ad-hoc networks (MANETs). This algorithm is based on some basic schemes such as RSA_CRT for encryption and decryption of messages; CRT for safety key generation, Shamir’s secret sharing principle for generation of secure routes. Those routes which are free from any malicious node and which belong to the set of disjoint routes between a source-destination pair are considered as probable routes. Shamir’s secret sharing principle is applied on those probable routes to obtain secure routes. Finally, most trustworthy and stable route is selected among those secure routes. Selection of the final route depends on some criteria of the nodes present in a route e.g.: battery power, mobility and trust value. In addition, complexity of key generation is reduced to a large extent by using RSA-CRT instead of RSA. In turn, the routing becomes less expensive and most secure and robust one. Performance of this routing protocol is then compared with non-secure routing protocols (AODV and DSR), secure routing scheme using secret sharing, security routing protocol using ZRP and SEAD depending on basic characteristics of these protocols. All such comparisons show that RSRP shows better performance in terms of computational cost, end-to-end delay and packet dropping in presence of malicious nodes in the MANET, keeping the overhead in terms of control packets same as other secure routing protocols.